1959
DOI: 10.1152/ajplegacy.1959.196.4.811
|View full text |Cite
|
Sign up to set email alerts
|

The pH of K-deficient muscle

Abstract: The acid-base balance of muscle from control and K-deficient rats was studied. From the measured buffering capacity, 8–11 mEq excess of anions or deficit of cations would be required to acidify 100 gm fat-free dry weight of muscle, 0.5 pH units. No evidence of increased organic acids, increased anionic equivalence of muscle proteins, or of decreased concentrations of weak bases which are potential cations in cell acidosis was found. This evidence, supplemented with data in the literature, fails to account for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
6
1

Year Published

1965
1965
1969
1969

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 0 publications
3
6
1
Order By: Relevance
“…Recent studies, however, failed to demonstrate intracellular acidosis in potassium-deficient muscle (7) and showed that anions and cations other than potassium and sodium play a role in cellular pH regulation (6). In the present studies the sum of intracellular potassium and sodium of potassium-deficient muscle was smaller than that of normal muscle only in experiment IA.…”
contrasting
confidence: 70%
See 3 more Smart Citations
“…Recent studies, however, failed to demonstrate intracellular acidosis in potassium-deficient muscle (7) and showed that anions and cations other than potassium and sodium play a role in cellular pH regulation (6). In the present studies the sum of intracellular potassium and sodium of potassium-deficient muscle was smaller than that of normal muscle only in experiment IA.…”
contrasting
confidence: 70%
“…Disappearance of plasma abnormalities following the acute administration of potassium chloride to nephrectomized potassiumdeficient rats (2) seemed to support this hypothesis, as did the finding by some investigators (3)(4)(5) of a decrease of intracellular pH in potassiumdeficient compared with normal skeletal muscle. Other workers, however, failed to find evidence of intracellular acidosis in potassium-deficient muscle (6,7).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Other investigators (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), however, using either * Submitted for publication August 19, 1965; accepted February 17, 1967. Supported in part by grants 5 TI AM-5028 and 5 TI HE-5469 from the National Institutes of Health.…”
Section: Introductionmentioning
confidence: 99%